2018
DOI: 10.6018/ijes/2018/2/319731
|View full text |Cite
|
Sign up to set email alerts
|

Child task-supported interaction in the Spanish EFL setting. Research and challenges

Abstract: Task-based language teaching research has expanded substantially in foreign language (FL) contexts but most research studies have been carried out with young adults in university settings, despite the fact that FL programs for children are on the increase worldwide. However, there is a clear lack of research-based evidence of what children actually do while performing tasks, which is crucial in order to make decisions about appropriate educational provision, to inform policy makers, and to maximize children's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 96 publications
1
4
0
1
Order By: Relevance
“…On one hand, the findings indicating positive attitudes and gains from jointly implementing content and task-based methods, especially within the frameworks of cooperative and/or collaborative learning, are in consonance with of experimental research on the effectiveness of content-based, cooperative and collaborative language teaching methods (Eriksson, 2018;Mayo, 2018;Mohamadpour et al 2018;Sato et al, 2017;Seah, 2020;Spenader et al, 2018). One example is Arboleda-Arboleda and Castro-Garcés' (2019) study which focuses on teaching the target language through literature and provides evidence for the effectiveness of content-based with task-based approaches.…”
Section: Discussionsupporting
confidence: 73%
“…On one hand, the findings indicating positive attitudes and gains from jointly implementing content and task-based methods, especially within the frameworks of cooperative and/or collaborative learning, are in consonance with of experimental research on the effectiveness of content-based, cooperative and collaborative language teaching methods (Eriksson, 2018;Mayo, 2018;Mohamadpour et al 2018;Sato et al, 2017;Seah, 2020;Spenader et al, 2018). One example is Arboleda-Arboleda and Castro-Garcés' (2019) study which focuses on teaching the target language through literature and provides evidence for the effectiveness of content-based with task-based approaches.…”
Section: Discussionsupporting
confidence: 73%
“…Se adopta además un enfoque orientado a la acción, puesto que se parte de la consideración del alumnado que aprende una lengua extranjera como agente social, es decir, como miembro de una sociedad que tiene tareas que llevar a cabo, no solo de tipo lingüístico, en unas circunstancias determinadas, en un entorno específico y dentro de un campo de acción concreto (Consejo de Europa, 2018). Desde este enfoque se promueve su participación mediante actividades donde prima la interacción en parejas o en pequeños grupos, dada la importancia de la misma en el aprendizaje gramatical y la adquisición de segundas lenguas (García Mayo, 2018;Long, 1996). A través de la interacción, se pretende promover y explicitar su reflexión metalingüística sobre la lengua extranjera y otras lenguas.…”
Section: Características Generales De Las Sdgeunclassified
“…Although recent studies on peer interaction have contributed to our knowledge of the nature of pairings, much is still unknown about the various factors which influence peer interaction in the primary English classroom. Light and Littleton (1998) for example have suggested that mutuality is more likely to be higher amongst pairs who are friends, but Garcia Mayo (2018) claims that pairs who choose to work together exhibit more off-task behaviour than teacher-selected pairs. Further studies with an impact for pedagogical practices could usefully be carried out on how learner motivation changes in relation to task type or learner pairing.…”
Section: Conclusiónmentioning
confidence: 99%